Pengembangan Media Visual Tentara Pada Pembelajaran Ilmu Pengetahuan Alam bagi Siswa Sekolah Dasar - Rizki Ahmad Luthfi; Sutrisno Sahari; Dhian Dwi Nur Wenda (AL-ASASIYYA: Journal Of Basic Education, 2022)
Based on the results of observations that teacher learning has not used learning media so that students are less active and easily bored so that students do not understand the concept of the solar system material so that student learning outcomes on average are still below the KKM 70, only 10% of students complete from all students. This research uses research and development (RD) which has the aim of producing a product and testing the validity, practicality, and effectiveness of the product in the form of military visual media (about the solar system). The stages of this research refer to the ADDIE design model (analysis, design, development, implementation, evaluation). This study concludes that the results of developing military visual media using data on validity, practicality and effectiveness get the following results, (1) army media is declared valid, with an average combined validity percentage of 85% which includes valid validity criteria may be used after minor revisions, (2) the practicality of army media is stated to be practical based on a questionnaire from the teacher's response with an average of 97.5% and an average student response questionnaire of 95.2% which includes very practical criteria and can be used without revision. (3) the effectiveness of army media is declared effective based on the posttest obtaining an average of 84.9% which states that the military media developed has been effective based on the results of scores above the predetermined KKM, which is 70%.